A Novel Human TGF-β1 Fusion Protein in Combination with rhBMP-2 Increases Chondro-Osteogenic Differentiation of Bone Marrow Mesenchymal Stem Cells - Claros-Gil, Silvia; Rico-Llanos, Gustavo Adolfo; Becerra-Ratia, José; Andrades-Gómez, José Antonio (MDPI, 2014)
Transforming growth factor-beta (TGF-β) is involved in processes related to the differentiation and maturation of osteoprogenitor cells into osteoblasts. Rat bone marrow (BM) cells were cultured in a collagen-gel containing 0.5% fetal bovine serum (FBS) for 10 days in the presence of rhTGF (recombinant human TGF)-β1-F2, a fusion protein engineered to include a high-affinity collagen-binding decapeptide derived from von Willebrand factor. Subsequently, cells were moderately expanded in medium with 10% FBS for 4 days and treated with a short pulse of rhBMP (recombinant human bone morphogenetic protein)-2 for 4 h. During the last 2 days, dexamethasone and β-glycerophosphate were added to potentiate osteoinduction. Concomitant with an up-regulation of cell proliferation, DNA synthesis levels were determined. Polymerase chain reaction was performed to reveal the possible stemness of these cells. Osteogenic differentiation was evaluated in terms of alkaline phosphatase activity and mineralized matrix formation as well as by mRNA expression of osteogenic marker genes. Moreover, cells were placed inside diffusion chambers and implanted ubcutaneously into the backs of adult rats for 4 weeks. Histological study provided evidence of cartilage and bone-like tissue formation. This experimental procedure is capable of selecting cell populations from BM that, in the presence of rhTGF-β1-F2 and rhBMP-2, achieve skeletogenic potential in vitro and in vivo.
Keywords: Ingeniería de tejidos; Huesos; Stem/progenitor cells; Three-dimensional (3D) culture; Transforming growth factor-b1 (TGF-b1); Bone morphogenetic protein-2 (BMP-2); Osteogenesis; Chondrogenesis